Sex differences in mortality and hospitalization in heart failure with preserved and mid-range ejection fraction: a systematic review and meta-analysis of cohort studies - You Deng; Jun Zhang; Jitao Ling; Qingwen Hu; Tianggang Song; Yi Xu; Menglu Liu; Yuting Wu; Kaibo Mei; Jiawei Chen; Huilei Zhao; Xiao Liu (Frontiers in Cardiovascular Medicine, 2024)
IntroductionThe influence of sex on the prognosis of heart failure with preserved or intermediate ejection fraction (HFpEF and HFmrEF) remains uncertain. This study aimed to investigate whether sex differences impact the prognosis of patients diagnosed with HFpEF and HFmrEF.MethodsA comprehensive search across three databases (PubMed, the Cochrane Library, and Embase) was conducted to identify sex-related prognostic cohort studies focusing on HFpEF and HFmrEF. Risk estimates were synthesized using the random effects model. The analysis included 14 cohorts comprising 41,508 HFpEF patients (44.65% males) and 10,692 HFmrEF patients (61.79% males).ResultsAmong HFpEF patients, men exhibited significantly higher rates of all-cause mortality (13 studies; hazard ratio (HR): 1.24, 95% confidence interval (CI): 1.15 to 1.33)) and cardiovascular disease mortality (5 studies; HR: 1.22, 95% CI: 1.14 to 1.31) compared to women. However, no significant difference was observed in HF admissions. For HFmrEF patients, men displayed notably higher all-cause mortality (HR: 1.21, 95% CI: 1.12 to 1.31) but no significant differences in cardiovascular mortality or HF admissions.DiscussionThese findings suggest that male patients diagnosed with HFpEF and HFmrEF may face a more unfavorable prognosis in terms of all-cause mortality. Variations were noted in cardiovascular mortality and HF admissions, indicating potential complexities in sex-related prognostic factors within these heart failure categories. In summary, male patients with HFpEF and HFmrEF may have a more unfavorable prognosis.